Investigation of different activation methods in peroxymonosulfate oxidation for the treatment of chemical industry wastewater - Sagir, Dilan; Ozen, Irem; Cene, Gulay Arslan; Guvenc, Senem Yazici; Can-Guven, Emine; Varank, Gamze; Cifci, Deniz Izlen (ELSEVIER SCI LTD, 2025)
The chemical industry produces complex and toxic wastewater that is difficult to treat with traditional methods. In a pioneering effort, this study provides the first systematic comparison of peroxymonosulfate (PMS)-based advanced oxidation processes (AOPs) using four distinct activation methods-iron (Fe2+), heat, ultraviolet (UV), and electric current (EC)-for the treatment of this challenging wastewater. The chemical oxygen demand (COD) removal efficiency with a single PMS application was 18.0 %, which increased to 54.2 %, 41.4 %, 51.6 %, and 82.1 % with Fe/PMS, Heat/PMS, UV/PMS, and EC/PMS, respectively. Using the Box-Behnken Design (BBD) to determine optimum conditions, validation experiments yielded COD removal rates of 59.5 % for Fe/PMS, 47.5 % for Heat/PMS, 57 % for UV/PMS, and 91 % for EC/PMS. Additionally, UV254 removal rates were 83.8 %, 78.5 %, 83.0 %, and 94.5 %, respectively. The treatment costs were calculated as 4.66 /kg COD for Fe/PMS, 2.60 /kg COD for Heat/PMS, 2.40 /kg COD for UV/PMS, and 0.43 /kg COD for EC/PMS. Among the methods compared, the EC/PMS system emerged as the most efficient and cost-effective process, achieving a remarkable 91 % COD removal at a minimal cost. These findings confirm that the activator type has a strong impact on the performance of PMS-based AOPs and highlight the utility of BBD in optimizing these processes.
Keywords: Advanced oxidation; Chemical industry wastewater; Industrial wastewater treatment; Peroxymonosulfate; Process optimization; ELECTROCHEMICAL ACTIVATION; PERSULFATE OXIDATION; ANTIBIOTIC SULFAMETHOXAZOLE; ENHANCED DEGRADATION; INORGANIC ANIONS; BISPHENOL-A; REMOVAL; SULFATE; ANODE; PEROXYDISULFATE; Engineering